2017
DOI: 10.5334/jbr-btr.1158
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic Meniscus and Cruciate Ligament Tears in Young Patients: A Comparison of 3T Versus 1.5T MRI

Abstract: Objective:To compare diagnosis value of 1.5T and 3T MRI in the detection of traumatic knee injuries in young patients by reference to arthroscopy.Materials and Methods:One hundred patients were prospectively included. All patients randomly underwent standardized knee 1.5T or 3T MRI with subsequent knee arthroscopy. Meniscus and cruciate ligaments tears were blindly assessed by two independent musculoskeletal radiologists.Results:Comparison of 1.5T and 3T MRI groups in the diagnosis of medial and lateral menisc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Other factors, such as imaging planes, sequence type, parameter settings, and coil technology took an equally important role in the diagnostic quality of MRI examinations. The prospective study of Nouri et al showed that 3.0 T MRI of the knee does not improve diagnosis accuracy compared with 1.5T MRI for detecting meniscal lesions [20].…”
Section: Discussionmentioning
confidence: 99%
“…Other factors, such as imaging planes, sequence type, parameter settings, and coil technology took an equally important role in the diagnostic quality of MRI examinations. The prospective study of Nouri et al showed that 3.0 T MRI of the knee does not improve diagnosis accuracy compared with 1.5T MRI for detecting meniscal lesions [20].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that higher field strength can improve MRI diagnostic accuracy; however, machines with higher field strength are not widely available, such machines are associated with increased costs, and higher field strength can cause increased artifacts from implanted hardware. 25 , 26 , 27 …”
Section: Discussionmentioning
confidence: 99%
“…Some authors have compared 1.5 T versus 3.0 T MRI for the visualisation of cartilage, tendons, and ligaments of different anatomical joints, but the results were controversial. Among these studies, some [28][29][30][31] did not find considerable improvements from 1.5 T to 3.0 T. On the other hand, other investigations [32][33][34] demonstrated higher image quality and better diagnostic performance of the 3.0 T MRI. From a technical point of view, the 3.0 T MRI has higher signal strength, but introduces artefacts due to field inhomogeneities [35].…”
Section: Introductionmentioning
confidence: 95%